Plasma levels of thrombin and activated protein C in patients with acute myocardial Infarction: An observational study - Becher, Tobias; Schimanski, Robert; Müller, Jens; Baumann, Stefan; Klenantz, Selina; Pötzsch, Bernd; Loßnitzer, Dirk (International journal of cardiology. Heart & vasculature, 2022)
Introduction - Activation of the plasmatic coagulation system is a major contributor to acute myocardial infarction (AMI). Markers of plasmatic coagulation and thrombin activation are correlated with clinical, laboratory and outcome parameters. In this study, we sought to evaluate if the catalytically active coagulation factors thrombin and activated protein C (APC) can be measured in patients with AMI and whether there are associations with laboratory or clinical parameters. - Methods - Thrombin and APC was quantified using oligonucleotide-enzyme-capture assays (OECAs) in 132 patients presenting with AMI immediately before and 24 h after percutaneous coronary intervention (PCI). - Results - APC was measured above the lower limit of quantification (LLOQ) in 43 (32.6%) patients before PCI (day 0) and in 55 (41.7%) patients on the following day (day 1). Thrombin was measured in 62 (47.0%) patients on day 0 and 60 (45.5%) on day 1. Both APC and thrombin were correlated with markers of thrombin generation including F1 + 2 and TAT. Additionally, APC values correlated with CK and CK-MB while thrombin correlated with CK and troponin I after PCI. APC levels above a cutoff of 0.141 ng/ml after PCI, but not thrombin, predicted 30 day major adverse cerebrovascular events. - Conclusion - Both thrombin and APC were elevated above the LLOQ in a subset of patients with AMI before and after PCI and correlated with surrogate markers of myocardial injury. Our results indicate that enzymatically active APC and thrombin are present in the circulation of patients with AMI.
Gesehen am 01.08.2023